Mechanical, thermal, and structural investigations of chemically strengthened Na2O–CaO–Al2O3–SiO2 glasses - Karlsson, Stefan; Mathew, Renny; Ali, Sharafat; Paemurru, Mart; Anton, Johan; Stevensson, Baltzar; Edén, Mattias (Frontiers in Materials, 2022)
For a series of conventional soda-lime-silicate glass with increasing Al2O3 content, we investigated the thermal, mechanical, and structural properties before and after K+-for-Na+ ion-exchange strengthening by exposure to molten KNO3. The Al-for-Si replacement resulted in increased glass network polymerization and lowered compactness. The glass transition temperature (Tg), hardness (H) and reduced elastic modulus (Er), of the pristine glasses were enhanced monotonically for increasing Al2O3 content. H and Er increased linearly until roughly equal stoichiometric amounts of Na2O and Al2O3 where nonlinear dependence on Al2O3 was observed, whereas H and Er of the chemically strengthened (CS) glasses revealed a strictly linear dependence. Tg on the other hand showed linear increase with Al-for-Si for pristine glasses while for the CS glasses a linear to nonlinear trend was observed. Solid-state 27Al nuclear magnetic resonance (NMR) revealed sole presence of AlO4 groups in both the pristine and CS glasses. 23Na NMR and wet-chemical analysis manifested that all Al-bearing glasses had a lower and near-constant K+-for-Na+ ion exchange ratio than the soda-lime-silicate glass. Differential thermal analysis of CS glasses revealed a “blurred” glass transition temperature (Tg) and an exothermic step below Tg; the latter stems from the relaxation of residual compressive stresses. The nanoindentation-derived hardness at low loads and <5 mol% Al2O3 showed evidence of stress relaxation for prolonged ion exchange treatment. The crack resistance is maximized for molar ratios n(M(2)O)/n(Al2O3)≈1 for the CS glasses, which is attributed to an increased elastic energy recovery that is linked to the glass compactness.